Comparative analysis of CDR3 regions in paired human αβ CD8 T cells. Issue 8 (12th July 2019) - Yu, Kun; Shi, Ji; Lu, Dan; Yang, Qiong
Abstract : The majority of human CD8 cytotoxic T lymphocytes express αβ T‐cell receptors that recognize peptide–MHC class I complexes. Considerable attention has been devoted to TCR β repertoires, but study of TCR α chains has been limited. To gain a better understanding of the features of CDR3α and CDR3β in paired samples, we comprehensively analyzed 776 unique paired αβ TCR CDR3 regions in this study. We found that (I) the CDR3 length among paired αβ TCRs had a fairly narrow distribution due to random assortment of CDR3 length in alpha and beta chains; (II) nucleotide deletions among CDR3 regions were positively correlated with insertions in both α and β TCRs; (III) the CDR3 loops of both α and β chains contained an abundance of charged/polar residues and the CDR3 base regions contained a conserved motif; and (IV) the occurrence of Gly was CDR3 length‐ and position‐dependent in both chains, whereas the frequency of Ser at positions 106 and 107 was positively correlated with CDR3 length in TCR β. Overall, the amino acids in CDR3 loop regions were significantly different between TCR α and β, which suggests a distinct role for each chain in the recognition of antigen–MHC complexes. Here, we have provided detailed information on CDR3 in paired TCRs expressed on human CD8+ T cells and established the basis of a reference set for αβ TCR repertoires in healthy humans. Abstract : The majority of T cells express a T‐cell receptor (TCR) made up of two chains, the TCR α  and TCR β, which recognize peptide–MHC class I complexes. In this study, we focus on analysis of features of the CDR3 region in paired TCRs expressed on human CD8 T cells. We found that the pairing of CDR3 alpha and beta chains is not random.